Strain sensor based on multi-layer wrinkled structure and preparation method and application thereof

By using a capacitive strain sensor designed with a multi-layer wrinkle structure, the combination of Cu@Pt film and PVDF material is used to solve the problem of low sensitivity of existing capacitive strain sensors, achieving high sensitivity and wide detection range effects. in a variety of application fields.

CN119437029AInactive Publication Date: 2025-02-14LUOYANG INST OF SCI & TECH

Patent Information

Application Number
CN202510032320.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The sensitivity of existing capacitive strain sensors is relatively low, especially in practical applications, which is difficult to meet the high sensitivity requirements.

Method used

Capacitive strain sensor designed with multi-layer wrinkle structure, using flexible dielectric insulating tape and flexible layered film electrode, combined with platinum-modified copper nanowire film (Cu@Pt film) and polyvinylidene fluoride (PVDF) material to form High sensitivity conductive film.

Benefits of technology

It realizes strain sensors with high sensitivity and wide detection range, overcomes the shortcomings of existing material selection, and is suitable for the fields of motion monitoring, health monitoring and information transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119437029A_ABST
    Figure CN119437029A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sensors, in particular to a strain sensor based on a multi-layer wrinkled structure and a preparation method and application thereof.The sensor simulates a skin wrinkled structure and belongs to a capacitive sensor, the sensor comprises a flexible medium insulating tape and two layers of flexible layered film electrodes, the flexible layered film electrodes are respectively positioned on two sides of the flexible dielectric insulating tape and cover the flexible dielectric insulating tape, and the flexible layered film electrodes are formed by combining a platinum-modified copper nanowire film (Cu (at) Pt film) with a flexible substrate material polyvinylidene fluoride (PVDF) as a conductive layer. The sensor has high sensitivity and a wide stretching range, overcomes the defects in existing material selection, and has potential application in the fields of exercise monitoring, health monitoring and information transmission.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of capacitive sensors, and in particular to a strain sensor based on a multi-layer pleated structure and a preparation method and application thereof. Background Art

[0002] With the rapid development of artificial intelligence and the Internet of Things, flexible wearable sensors have attracted widespread attention in the fields of motion monitoring, health monitoring, human-computer interaction, etc. According to different sensing mechanisms, flexible sensors are divided into four types: resistive, capacitive, piezoelectric, and triboelectric. Among them, capacitive sensors have been widely studied due to their simple structure, good anti-interference and strong adaptability. So far, many researchers have been committed to improving the sensitivity of capacitive sensors. Sensitivity can be expressed by gauge factors (GF). The larger the GF, the higher the sensitivity. A search of prior art literature found that the literature “A Highly Elastic, Capacitive Strain Gauge Based on Percolating Nanotube Networks” (Nano Letters. 2012, 12 (4), 1821−1825) and the literature “Highly stretchable conductors and piezocapacitive strain gauges based on simple contact-transfer patterning of carbon nanotube forests” (Carbon. 2014, 80, 396−404) used carbon nanotube conductive networks as stretchable electrodes and silicon-based elastomers as stretchable substrates, and achieved a GF of 1 under 100% and 150% strain. The paper "Batch Fabrication of Customizable Silicone-Textile Composite Capacitive Strain Sensors for Human Motion Tracking" (Advanced Materials Technologies. 2017, 2, 1700136) produced a new type of conductive material by combining conductive textile electrodes and silicon-based dielectrics, achieving a GF of 1.23 at 100% stretching. However, the sensitivity of capacitive strain sensors is still low, especially in practical applications. Therefore, it is imperative to develop capacitive sensors with higher sensitivity. Summary of the invention

[0003] To solve the above problems, the purpose of the present invention is to provide a strain sensor based on a multi-layer folded structure and a preparation method and application thereof, starting from the structural design of the sensor device. The sensor is a bionic skin folded structure and belongs to a capacitive sensor. The sensor includes a flexible dielectric insulating tape and a flexible layered film electrode, wherein the flexible layered film electrode is two layers, which are respectively located on both sides of the flexible dielectric insulating tape and cover the flexible dielectric insulating tape, wherein the flexible layered film electrode is a copper nanowire film (Cu@Pt film) modified with platinum with excellent conductivity as a conductive layer combined with a flexible substrate material polyvinylidene fluoride (PVDF). The sensor has high sensitivity and a wide detection range, overcomes the shortcomings in the existing material selection, and has potential applications in the fields of motion monitoring, health monitoring and information transmission.

[0004] The present invention provides a method for preparing a strain sensor based on a multi-layer pleated structure, which specifically comprises the following steps: (1) Preparing a copper nanowire solution; (2) Preparation of Cu@Pt thin film; (3) Preparation of layered Cu@Pt / PVDF film: e. Using a hydrophobic material as a carrier, pick up the Cu@Pt film stored in ultrapure water, and then place the two together in an oven at 80°C for drying for more than 1 hour; f. Prepare a polyvinylidene fluoride (PVDF) solution, pour the PVDF solution on the Cu@Pt film supported on the hydrophobic material after drying, and rotate evenly on a coating machine; g. Place the Cu@Pt film after spin coating PVDF in an oven at 80°C and dry for more than 12 hours, and PVDF and Cu@Pt film together form a layered Cu@Pt / PVDF conductive film; h. The layered Cu@Pt / PVDF conductive film is torn off from the hydrophobic material and cut into multiple pieces for later use; (4) Preparation of multilayer wrinkled sensors: Take a flexible dielectric insulating tape and stretch it, then stick a layered Cu@Pt / PVDF conductive film on both sides of the flexible dielectric insulating tape so that the layered Cu@Pt / PVDF conductive film covers the flexible dielectric insulating tape, and then relax the flexible dielectric insulating tape to obtain a strain sensor with a multi-layer pleated structure.

[0005] Furthermore, step (1) is specifically as follows: 135 mg of cupric chloride dihydrate, 70 mg of ascorbic acid and 1.0 g of octadecylamine are dissolved in 140 mL of deionized water, and then stirred at room temperature at a speed of 500 r / min for 4 hours, and then the suspension obtained by stirring is transferred to a 200 mL hydrothermal reactor, and the hydrothermal reactor is placed in a 120° C. oven for reaction for 20 hours. After the reaction is completed, it is naturally cooled to room temperature, and then the obtained liquid is centrifuged with deionized water, and then the upper layer of liquid is poured off, and the obtained solid matter is centrifuged with n-hexane. Then, the obtained solid matter is centrifuged with isopropanol, and the finally obtained solid matter is dispersed in isopropanol to obtain a copper nanowire solution.

[0006] Furthermore, the centrifugal washing in step (1) is first centrifuged at a speed of 2000 r / min for 5 min, and then centrifuged at a speed of 12000 r / min for 2 min; Furthermore, step (2) specifically includes the following steps: a. Spray the copper nanowire solution onto a glass slide to form a thin film, place the glass slide in an oven at 60-80°C for 2 hours, and then soak the glass slide in an acetic acid solution. The copper nanowire film is separated from the glass slide and floats on the liquid surface for later use; b. Take another glass slide as a carrier, transfer the copper nanowire film into a platinum ion solution, and react at 25°C for 30s-2min, that is, replace a layer of platinum on the surface of the copper nanowire by chemical replacement to obtain a Cu@Pt film; c. Use a glass slide to absorb the Cu@Pt film and transfer it to a culture dish filled with ultrapure water. Let it stand for more than 30 minutes, then take out the Cu@Pt film and store it in ultrapure water for later use; Furthermore, in step (2) in step b, the platinum ion solution is an aqueous solution of chloroplatinic acid with a concentration of 0.01-0.1M.

[0007] Furthermore, in step (3) in step e, the hydrophobic material is polypropylene (PP).

[0008] Furthermore, in step (3), in step f, a polyvinylidene fluoride (PVDF) solution is prepared, specifically, the main agent polyvinylidene fluoride is mixed with the auxiliary agent N,N-dimethylacetamide, that is, the mass ratio of the main agent to the auxiliary agent is 1:10, and the polyvinylidene fluoride solution is obtained after stirring; the rotation speed of the sizing machine is 50-150r / min, and the rotation time is 50s.

[0009] Furthermore, in step (4), the stretching degree of the flexible dielectric insulating tape is 60%-240%.

[0010] The present invention also provides a strain sensor with a multi-layer pleated structure obtained according to the above preparation method. The strain sensor is widely used in the fields of motion monitoring, health monitoring and information transmission.

[0011] The strain sensor comprises a flexible dielectric insulating tape and a flexible layered Cu@Pt / PVDF conductive film, wherein the flexible layered Cu@Pt / PVDF conductive film is two layers, which are respectively located on both sides of the flexible dielectric insulating tape and cover the flexible dielectric insulating tape.

[0012] Compared with the prior art, the present invention has the following beneficial effects: The multilayer wrinkled strain sensor is prepared by dealloying technology. The strain sensor has high sensitivity and wide detection range, excellent performance, simple preparation process, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a sensitivity performance diagram of the Cu@Pt / PVDF strain sensor sample based on the multilayer wrinkled structure prepared in Example 1. DETAILED DESCRIPTION

[0014] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific embodiments and drawings. The following embodiments are implemented based on the technology of the present invention, and detailed implementation methods and operating steps are given, but the protection scope of the present invention is not limited to the following embodiments.

[0015] Embodiment 1: (1) Preparation of copper nanowire solution: 135 mg of copper chloride dihydrate, 70 mg of ascorbic acid and 1.0 g of octadecylamine were dissolved in 140 mL of deionized water, and then placed on a magnetic stirrer, stirred at a speed of 500 r / min for 4 h at room temperature to obtain a light blue suspension, and then the light blue suspension was transferred to a 200 mL hydrothermal reactor, and the hydrothermal reactor was placed in a 120 ° C oven for reaction for 20 h. After the reaction was completed, it was naturally cooled to room temperature to obtain a brick red liquid, and the brick red liquid was transferred to a centrifuge tube with a dropper and deionized water was added to 50 mL for centrifugal washing, and then the upper layer of liquid was poured out, and the obtained solid matter was centrifuged with n-hexane. After that, the obtained solid matter was centrifuged with isopropanol, and the upper layer of liquid was poured out, and the final solid matter was dispersed in 100 mL of isopropanol to obtain a copper nanowire solution, wherein the centrifugal washing was first centrifuged at a speed of 2000 r / min for 5 min, and then at a speed of 12000 r / min for 2 min; (2) Preparation of Cu@Pt thin film: a. Spray the copper nanowire solution onto a glass slide to form a thin film, place the glass slide in an oven at 60°C for 2 hours, and then soak the glass slide in an acetic acid solution. The copper nanowire film is separated from the glass slide and floats on the liquid surface for later use; b. Take another glass slide as a carrier, transfer the copper nanowire film to a 100 mL 0.1 M chloroplatinic acid aqueous solution (i.e., platinum ion solution), and react at 25°C for 30 seconds, that is, replace a layer of platinum on the surface of the copper nanowire by chemical replacement, which is recorded as Cu@Pt film; c. Use a glass slide to absorb the Cu@Pt film and transfer it to a culture dish filled with ultrapure water. Let it stand for more than 30 minutes to wash away the residual acid. Then take out the Cu@Pt film and store it in ultrapure water for later use. (3) Preparation of layered Cu@Pt / PVDF film: e. Using the hydrophobic material PP as a carrier, the Cu@Pt film stored in ultrapure water was picked up, and then the two were placed in an oven at 80°C for 1.5 hours to dry the water on the hydrophobic material PP and the Cu@Pt film; f. Prepare polyvinylidene fluoride (PVDF) solution, specifically, mix 20g of main agent polyvinylidene fluoride with 200g of auxiliary agent N, N-dimethylacetamide, that is, the mass ratio of the main agent to the auxiliary agent is 1:10, stir for 5 minutes, pour the PVDF solution on the Cu@Pt film supported on the hydrophobic material PP after drying, and rotate evenly on a coating machine, the coating machine speed is 50r / min, and the time is 50s; g. After the PVDF is spin-coated, the Cu@Pt film is placed in an oven at 80°C and dried for 12 hours to dry the PVDF. The PVDF and the Cu@Pt film together form a layered Cu@Pt / PVDF conductive film; h. Tear off the layered Cu@Pt / PVDF conductive film from the hydrophobic material PP and cut it into multiple pieces with a width of 1 cm and a length of 3.5 cm for later use; (4) Preparation of multilayer wrinkled sensors: Take a flexible dielectric insulating tape and stretch it by 240%. Then, a layered Cu@Pt / PVDF conductive film is pasted on both sides of the flexible dielectric insulating tape so that the layered Cu@Pt / PVDF conductive film covers the flexible dielectric insulating tape. Then, relax the insulating tape to obtain a strain sensor with a multi-layer pleated structure.

[0016] Figure 1 Figure 1 is a sensitivity performance diagram of the capacitive strain sensor sample based on the multilayer corrugated structure of Cu@Pt / PVDF prepared in Example 1. After testing, the capacitance of the flexible stretchable strain sensor with a multilayer corrugated structure of Cu@Pt / PVDF is as follows: Figure 1As shown, starting from the initial 0% stretching, △C / C0 increases until the capacitance change rate of the sample is the largest when stretched by 240%. At this time, the slope is the largest, the sensor sensitivity is the highest, and the performance is the best (stretching the strain sensor and testing the capacitance change rate belongs to the prior art and will not be repeated here). In addition, the GF of the Cu@Pt / PVDF capacitive strain sensor sample based on the multilayer pleated structure prepared in this embodiment is 1.47.

[0017] Embodiment 2: (1) Same as step (1) in Example 1; (2) Preparation of Cu@Pt thin film: a. Spray the copper nanowire solution onto a glass slide to form a thin film, place the glass slide in an oven at 70°C for 2 hours, and then soak the glass slide in an acetic acid solution. The copper nanowire film is separated from the glass slide and floats on the liquid surface for later use; b. Take another glass slide as a carrier, transfer the copper nanowire film to a 120 mL 0.01 M chloroplatinic acid aqueous solution (i.e., platinum ion solution), and react at 25°C for 1 min, that is, replace a layer of platinum on the surface of the copper nanowire by chemical replacement, which is recorded as Cu@Pt film; c. Use a glass slide to absorb the Cu@Pt film and transfer it to a culture dish filled with ultrapure water. Let it stand for more than 30 minutes to wash away the residual acid. Then take out the Cu@Pt film and store it in ultrapure water for later use. (3) Preparation of layered Cu@Pt / PVDF film: e. Using the hydrophobic material PP as a carrier, the Cu@Pt film stored in ultrapure water was picked up, and then the two were placed in an oven at 80°C for 2 hours to dry the water on the hydrophobic material PP and the Cu@Pt film; f. Prepare polyvinylidene fluoride (PVDF) solution, specifically, mix 25g of main agent polyvinylidene fluoride with 250g of auxiliary agent N, N-dimethylacetamide, that is, the mass ratio of the main agent to the auxiliary agent is 1:10, stir for 5 minutes, pour the PVDF solution on the Cu@Pt film supported on the hydrophobic material PP after drying, and rotate evenly on a sizing machine, the sizing machine speed is 100r / min, and the time is 50s; g. After the spin coating of PVDF, the Cu@Pt film was placed in an oven at 80°C for 13 hours to dry the PVDF, and the PVDF and the Cu@Pt film formed a layered Cu@Pt / PVDF conductive film together; h. Tear off the layered Cu@Pt / PVDF conductive film from the hydrophobic material PP and cut it into multiple pieces with a width of 1 cm and a length of 3.5 cm for later use; (4) Preparation of multilayer wrinkled sensors: Take a flexible dielectric insulating tape and stretch it by 120%. Then, a layered Cu@Pt / PVDF conductive film is pasted on both sides of the flexible dielectric insulating tape so that the layered Cu@Pt / PVDF conductive film covers the flexible dielectric insulating tape. Then, relax the insulating tape to obtain a strain sensor with a multi-layer pleated structure.

[0018] Embodiment 3: (1) Same as step (1) in Example 1; (2) Preparation of Cu@Pt thin film: a. Spray the copper nanowire solution onto a glass slide to form a thin film, place the glass slide in an oven at 80°C for 2 hours, and then soak the glass slide in an acetic acid solution. The copper nanowire film is separated from the glass slide and floats on the liquid surface for later use; b. Take another glass slide as a carrier, transfer the copper nanowire film to a 150 mL 0.01 M chloroplatinic acid aqueous solution (i.e., platinum ion solution), and react at 25°C for 2 min, that is, replace a layer of platinum on the surface of the copper nanowire by chemical replacement, which is recorded as Cu@Pt film; c. Use a glass slide to absorb the Cu@Pt film and transfer it to a culture dish filled with ultrapure water. Let it stand for more than 30 minutes to wash away the residual acid. Then take out the Cu@Pt film and store it in ultrapure water for later use. (3) Preparation of layered Cu@Pt / PVDF film: e. Using the hydrophobic material PP as a carrier, the Cu@Pt film stored in ultrapure water was picked up, and then the two were placed in an oven at 80°C for 2.5 hours to dry the water on the hydrophobic material PP and the Cu@Pt film; f. Prepare polyvinylidene fluoride (PVDF) solution, specifically, mix 15g of main agent polyvinylidene fluoride with 150g of auxiliary agent N, N-dimethylacetamide, that is, the mass ratio of the main agent to the auxiliary agent is 1:10, stir for 5 minutes, pour the PVDF solution on the Cu@Pt film supported on the hydrophobic material PP after drying, and rotate evenly on a coating machine, the coating machine speed is 150r / min, and the time is 50s; g. The Cu@Pt film after spin coating PVDF was placed in an oven at 80°C for 14 hours to dry the PVDF, and the PVDF and Cu@Pt film formed a layered Cu@Pt / PVDF conductive film together; h. Tear off the layered Cu@Pt / PVDF conductive film from the hydrophobic material PP and cut it into multiple pieces with a width of 1 cm and a length of 3.5 cm for later use; (4) Preparation of multilayer wrinkled sensors: Take a flexible dielectric insulating tape and stretch it by 60%. Then, a layered Cu@Pt / PVDF conductive film is pasted on both sides of the flexible dielectric insulating tape so that the layered Cu@Pt / PVDF conductive film covers the flexible dielectric insulating tape. Then, relax the insulating tape to obtain a strain sensor with a multi-layer pleated structure.

[0019] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a strain sensor based on a multi-layer pleated structure, characterized in that: The following steps are involved: (1) Preparing a copper nanowire solution; (2) Preparation of Cu@Pt thin film; (3) Preparation of layered Cu@Pt / PVDF film: e. Using a hydrophobic material as a carrier, pick up the Cu@Pt film stored in ultrapure water, and then place the two together in an oven at 80°C for drying for more than 1 hour; f. Prepare a PVDF solution, pour the PVDF solution on the Cu@Pt film supported on the hydrophobic material after drying, and rotate it evenly on a sizing machine; g. Place the Cu@Pt film after spin coating PVDF in an oven at 80°C and dry for more than 12 hours, and PVDF and Cu@Pt film together form a layered Cu@Pt / PVDF conductive film; h. The layered Cu@Pt / PVDF conductive film is torn off from the hydrophobic material and cut into multiple pieces for later use; (4) Preparation of multilayer wrinkled sensors: Take a flexible dielectric insulating tape and stretch it, then stick a layered Cu@Pt / PVDF conductive film on both sides of the flexible dielectric insulating tape so that the layered Cu@Pt / PVDF conductive film covers the flexible dielectric insulating tape, and then relax the flexible dielectric insulating tape to obtain a strain sensor with a multi-layer pleated structure.

2. The method for preparing a strain sensor based on a multi-layer pleated structure according to claim 1, characterized in that: Step (1) is as follows: 135 mg of copper chloride dihydrate, 70 mg of ascorbic acid and 1.0 g of octadecylamine are dissolved in 140 mL of deionized water, and then stirred at room temperature at a speed of 500 r / min for 4 hours. Then, the suspension obtained by stirring is transferred to a 200 mL hydrothermal reactor, and the hydrothermal reactor is placed in a 120° C. oven for reaction for 20 hours. After the reaction is completed, it is naturally cooled to room temperature, and then the obtained liquid is centrifuged with deionized water, and then the upper layer of liquid is poured off, and the obtained solid matter is centrifuged with n-hexane. Then, the obtained solid matter is centrifuged with isopropanol, and the finally obtained solid matter is dispersed in isopropanol to obtain a copper nanowire solution.

3. The method for preparing a strain sensor based on a multi-layer pleated structure according to claim 2, characterized in that: The centrifugal washing in step (1) is performed by first centrifuging at a speed of 2000 r / min for 5 min, and then centrifuging at a speed of 12000 r / min for 2 min.

4. The method for preparing a strain sensor based on a multi-layer pleated structure according to claim 1, characterized in that: Step (2) specifically includes the following steps: a. Spray the copper nanowire solution onto a glass slide to form a thin film, place the glass slide in an oven at 60-80°C for 2 hours, and then soak the glass slide in an acetic acid solution. The copper nanowire film is separated from the glass slide and floats on the liquid surface for later use; b. Take another glass slide as a carrier, transfer the copper nanowire film into a platinum ion solution, and react at 25°C for 30s-2min, that is, replace a layer of platinum on the surface of the copper nanowire by chemical replacement to obtain a Cu@Pt film; c. Use a glass slide to absorb the Cu@Pt film and transfer it to a culture dish filled with ultrapure water. Let it stand for more than 30 minutes, then take out the Cu@Pt film and store it in ultrapure water for later use.

5. The method for preparing a strain sensor based on a multi-layer pleated structure according to claim 4, characterized in that: In step (2) of step b, the platinum ion solution is an aqueous solution of chloroplatinic acid with a concentration of 0.01-0.1M.

6. The method for preparing a strain sensor based on a multi-layer pleated structure according to claim 1, characterized in that: In step (3) in step e, the hydrophobic material is polypropylene.

7. The method for preparing a strain sensor based on a multi-layer pleated structure according to claim 1, characterized in that: In step (3), in step f, a polyvinylidene fluoride solution is prepared, specifically, the main agent polyvinylidene fluoride is mixed with the auxiliary agent N,N-dimethylacetamide, that is, the mass ratio of the main agent to the auxiliary agent is 1:10, and the polyvinylidene fluoride solution is obtained after stirring; the rotation speed of the sizing machine is 50-150r / min, and the rotation time is 50s.

8. The method for preparing a strain sensor based on a multi-layer pleated structure according to claim 1, characterized in that: The stretching degree of the flexible dielectric insulating tape in step (4) is 60%-240%.

9. A strain sensor based on a multi-layered wrinkled structure obtained by the preparation method according to any one of claims 1 to 8.

10. Application of the strain sensor based on the multi-layer pleated structure as claimed in claim 9 in the fields of motion monitoring, health monitoring and information transmission.

Citation Information

Patent Citations

  • Flexible capacitive sensor based on silver nanowire material and preparation method thereof

    CN112985470A

  • Method for preparing Cu NW-coated NiO high-reliability flexible transparent electrode through full solution

    CN118039246A

Cited By

  • Flexible transparent diaphragm, electroacoustic conversion device and preparation method thereof

    CN120137231A